Our team Dr George Mahuku - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Dr George Mahuku, IITA plant pathologist for Eastern, Central and Southern Africa shares on IITA's research on controlling aflatoxins - a major global health problem that threatens lives and livelihoods.